Dimension reduction of subjective motivational values toward child gender tool tested in women of reproductive age from a hospital in rural area of Himachal Pradesh, India - Dinesh Kumar; Shabab Ahmad; Chirag Goel; Avi Kumar Bansal; Shripad Patil (Wolters Kluwer Medknow Publications, 2021)
Background: A novel subjective Motivational Value toward Child Gender (MVCG) tool was developed using the theoretical construct of 10 motivational domains described by Shalom H Schwartz. Objective: The study aimed to summarize the pattern of correlations of (MVCG) in women of reproductive age in Himachal Pradesh, India. Methods: A cross-sectional study was conducted from October 2018 to November 2019 among a sample of 355 women. Required data were collected through an interviewer-administered questionnaire. Maximum likelihood exploratory factor analysis (EFA) with oblique rotation was done with Bartlett's test sphericity and Kaiser-Meyer-Olkin test. Results: A total of 28 (53.8%) questions loaded on eight factors explaining maximum variance (68.7%). Reliability analysis of these questions, with high loadings on extracted factors, of the questionnaire, observed with poor Cronbach's alpha of 0.61 and intraclass cluster coefficient (ICC) 0.49. However, selected domains such as tradition, power, achievement, self-direction, and benevolence were observed with a good Cronbach's alpha and ICC. Conclusion: MCVG is novel tool in its kind with well scalable properties in measuring subjective motivational values towards child gender. After EFA, total questions across 10 domains reduced from 52 to 28, across 8 domains, loaded on 8 factors with good reliability and agreement.